The Effect of Thymoquinone Administration on Local Immunoglobulin-G Levels of Rattus norvegicus Strain Wistar Sciatic Nerve Crush Injury Model - Valentinus Besin; Abdul Hafid Bajamal; Mohammad Hasan Machfoed; Jusak Nugraha; Budi Utomo; Paulus Budiono Notopuro (The Indonesian Biomedical Journal, 2022)
BACKGROUND: Immunoglobulin-G (IgG) is a product of the initial response to secondary immune response, which accumulates in distal segment of the nerve after crush injury. Thymoquinone modulates the adaptive immune response. Effect of thymoquinone administration on local IgG levels of Rattus norvegicus Wistar rats sciatic nerve crush injury model has not been elucidated.METHODS: This was an experimental study, with 63 Rattus norvegicus Wistar rats that divided into 9 groups. Three groups were given placebo, 3 groups were given 100 mg/kg/day thymoquinone, and 3 groups were given 250 mg/kg/day thymoquinone. The rats were terminated based on the assigned group at 5x24, 6x24, and 7x24 hours and then the IgG levels were measured using sandwich enzyme-linked immunosorbent assay (ELISA).RESULTS: There was a significant difference in IgG levels after administration of 100 and 250 mg/kg/day thymoquinone at 5x24 hours and 7x24 hours post-injury compared to the rats that were given no treatment. A significant difference of IgG levels was also found after administration of 100 mg/kg/day thymoquinone group at 6x24 hours post-injury. Critical point of decreasing local IgG of all groups happened at 6x24 hours after injury, however, there was no significant difference in the median levels of thymoquinone at doses of 100 mg/kg and 250 mg/kg.CONCLUSION: Local IgG levels in distal segment of the sciatic nerve crush injury is lower in rats that were given 100 mg/kg thymoquinone treatment compared to the rats that receive no thymoquinone treatment since 5x24 hours after injury. Thymoquione administration should be given immediately after the crush injury until before 6x24 hours post-injury to decrease antibodies in degeneration process.KEYWORDS: thymoquinone, immunoglobulin-G, crush injury, sciatic nerve